Young Climate Protesters’ Mobilization Availability: Climate Marches and School Strikes Compared - Rainsford, Emily; Saunders, Clare (Frontiers in Political Science, 2021)
Although there is a developing strand of literature on young people’s participation in environmental activism, there have been few systematic comparisons of their participation in different forms of environmental activism. This article compares the participation of young people and their older counterparts in climate change marches and Global Climate Strikes (GCSs). The agential and structural factors that draw people into protest participation are, in general terms, well recognized. However, it is also recognized that the factors that lead to particular types of protest on certain issues might not be the same as those that lead to different types of protest on different issues. In this article, we keep the protest issue constant (climate change), and make comparisons across different forms of climate protest (marches and school strikes). We coin the term “mobilization availability”, which is a useful way to understand why young people are differentially mobilized into different types of climate change protest. Our notion of mobilization availability invites scholars to consider the importance of the interplay of the supply and demand for protest in understanding who protests and why. We analyse data collected using standardized protest survey methodology (n = 643). In order to account for response rate bias, which is an acute problem when studying young people’s protest survey responses, we weighted the data using propensity score adjustments. We find that the youth-oriented supply of protest evoked by GCS mobilized higher numbers of young people into climate protest than did the more adult-dominated climate marches. GCS did this by providing accessible forms of protest, which reduced the degree of structural availability required to encourage young people to protest on the streets, and by emotionally engaging them. Indeed, the young people we surveyed at the GCSs were considerably more angry than their adult counterparts, and also angrier than young people on other climate protests. Our conceptual and empirical innovations make this paper an important contribution to the literature on young people’s political participation.